Analisis Praktik PPP Dalam Pengelolaan Program Internet Ponorogo Masuk RT (INPOMASE) - Naomi Susilowati; Deby Febriyan Eprilianto; Muhammad Farid Ma'ruf; Galih Wahyu Pradana (Kolaborasi : Jurnal Administrasi Publik, 2022)
The Ponorogo RT Internet Program (INPOMASE) is a free internet program for every RT in Ponorogo Regency. So that the District Government cooperates with the private sector through the concept of Public Private Partnership (PPP, namely with PT Lentera Digital Nusantara. The purpose of this study is to identify and describe Public Private Partnership in the management of the Ponorogo Internet Program Entering RT. In the implementation of the Public Private Partnership there are 9 stages implementation of the agreement, namely project selection, public consultation, feasibility study, risk review, forms of cooperation, government support, procurement, implementation, and supervision. The method used in this study is descriptive with a qualitative approach. Data analysis techniques use interactive models according to Milles and Hubberman which consists of data collection, data reduction, data presentation, drawing conclusions, and verification.The results show that when viewed from the procedures established by the Coordinating Ministry for the Economy regarding the stages of the Public Private Partnership being carried out The relationship between the Ponorogo Regency Government and PT Lentera Digital Nusantara did not meet the stipulated provisions, because there were stages in the form of cooperation and procurement that were not implemented. The existence of this collaboration is the initiation of the Regent of Ponorogo as the regional leader who appointed PT Lentera Digital Nusantara as the provider of the internet network in Ponorogo.